2020
DOI: 10.1001/jamanetworkopen.2020.4819
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Performance of a Point-of-Care Test for Chlamydia and Gonorrhea

Abstract: IMPORTANCERates of chlamydial and gonococcal infection continue to increase in the United States, as do the associated costs of untreated infections. Improved diagnostic technologies that support testing and treating in 1 clinical visit are critical to advancing efforts to control the rates of chlamydial and gonococcal infection. OBJECTIVE To evaluate the clinical performance of a point-of-care (POC) molecular diagnostic assay for the detection of chlamydia and gonorrhea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 20 publications
0
38
0
Order By: Relevance
“…1 ). Finally, 39 articles were included in this systematic review and meta-analysis [ [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). Finally, 39 articles were included in this systematic review and meta-analysis [ [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Recently, some new molecular POC diagnostic technology (such as the io CT/NG Assay, the Visby Medical Sexual Health Test and the rapid multiplex PCR assays.) has been developed and meets many of the requirements of the TPP for a POC device (sensitive, specific, rapid), which could represent important advances in the development of rapid diagnostics for sexually transmitted infections [ 61 , 62 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…New developments in point-of-care tests, mobile health, home sampling and internet testing offer increasing opportunities to implement widespread testing to detect asymptomatic chlamydia infections, including extragenital infections. [6][7][8] However, the clinical and public health relevance of active case finding by testing for asymptomatic infections is under debate. [9][10][11] The balance between benefits and harms of testing for asymptomatic infections might be changing for three reasons: (1) empirical evidence does not support the claim that enhanced testing of asymptomatics reduces the incidence and prevalence of chlamydia infection; (2) the risk of long-term complications attributable to a chlamydia infection in particular the risk of tubal factor infertility (TFI) is considered low and there is uncertainty about the fraction that can be prevented by routine testing; (3) there is more acknowledgement of the harms related to overdiagnosis and overtreatment, including the potential for antimicrobial resistance in other pathogens.…”
Section: Problem Analysismentioning
confidence: 99%
“…It is a molecular POC test for CT and NG. 30 ,31s A pilot study for detection of CT using the assay found high sensitivity and specificity and high patient acceptability, and indicated that 70% of women preferred to self-collect vaginal swabs if a POC test was available. 32s This POC assay is the first amplification assay to provide a sample to result in 30 minutes (including DNA extraction); this turnaround time would allow clinicians to treat infected patients before they leave most clinical encounters.…”
Section: Resultsmentioning
confidence: 99%